The Effect of ESG Disclosure, Green Investment, and Board Gender Diversity on Corporate Reputation - Razaq, Muhammad; Wati, Lela Nurlaela (Jurnal Ragam Pengabdian, 2026)
This study investigates how ESG disclosure, green investment, and board gender diversity influence corporate reputation within Indonesia's manufacturing industry. The research draws on secondary data sourced from the annual and sustainability reports of companies listed on the Indonesia Stock Exchange between 2018 and 2024. A sample of 68 companies yielding 476 total observations was analyzed using binary logistic regression with the Maximum Likelihood approach, processed through EViews 12.The findings reveal that ESG disclosure and board gender diversity both positively and significantly affect corporate reputation, indicating that greater ESG transparency and a more gender-inclusive boardroom improve how stakeholders perceive a company. Green Investment, however, showed no significant impact on reputation — a result that may stem from insufficient disclosure, delayed outcomes, and inconsistent practices among companies. The study concludes that to build a stronger corporate reputation, companies should prioritize improving the quality of their ESG disclosure and adopt more inclusive governance structures.